THE INFLUENCES OF GENDER INEQUALITY TOWARD SELF-ACTUALIZATION IN THE NOVEL A THOUSAND SPLENDID SUNS BY KHALED HOSSEINI - Febrianti, Dwi Selfi; Rosmiati (Prologue: Journal on Language and Literature, 2024)
This research studies of the influences of gender inequality toward self- actualization in the novel A Thousand Splendid Suns by Khaled Hosseini. The Objectives of the studies are 1) to describe the type of gender inequality depicted in the Novel A Thousand Splendid Suns and 2) to elaborate the influence of gender inequality toward Self-Actualization in the novel A Thousand Splendid Suns. There are two theories used in this study which are Gender Inequality by Mansour Fakih and Humanistic Psychology by Abraham Maslow. The methodology used by the researcher is qualitative research. This study analyzes data collected from quotes and narratives to find types of gender inequality that can affect a person's self-development, especially in achieving self-actualization. The analysis of this research focuses on the concept of gender inequality and self-actualization. The data collected from the material object of this research provides an overview of the forms of gender inequality that must be experienced by female characters in the novel. Through this research it was found that gender inequality can negatively affect self - actualization achievement. There are some evidences and proofs of type of gender inequality depicted on the novel such as Women Subordination, violence, women stereotyping, and marginalization.